Association of Householder Smoking With Poverty and the Mediating Effect of NCDs in Relatively Underdeveloped Regions in China - Yang, Huimin; Chen, Bowen; Guo, Aili; Song, Jiarui; Cheng, Xi; Jin, Chenggang (Frontiers in Public Health, 2022)
Background: Studies have not provided clear enough evidence on the direct association between cigarette smoking and poverty. This study aims to assess the association of householder smoking with near-poverty households, and the potential mediating effect of NCDs. Methods A cross-sectional survey was conducted from November 2019 to October 2020 in relatively underdeveloped regions in China. In total, 2,409 households were investigated in areas under the jurisdiction of 24 primary health care (PHC) institutions of eight provinces. Pearson's χ2-test was performed, and multivariable logistic regression and extended probit regression models were fitted to examine the association between householder smoking and near-poverty households. Moreover, generalized structural equation modeling was used to explore the mediating effect of NCDs. Results After adjusting for all other potential confounding factors, compared with households headed by never-smokers, households headed by smokers exhibited significantly elevated risks of being near poverty, with an odds ratio of 2.01 (95% CI: 0.48–0.91). We also found that living in rural areas and having a low education level both had a negative effect on being near poverty. Additionally, NCDs had a significantly positive mediating effect, with a 31.57% effect of householder smoking on near-poverty status mediated by NCDs; the indirect effect was estimated to be 0.17 (95% CI: 0.04–0.31). Conclusions Householder smoking significantly elevated the risk of the household being near poverty, and suffering NCDs had a positive mediating effect.